If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -13z = 0 Combine like terms: z + -13z = -12z -12z = 0 Solving -12z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '-12'. z = 0 Simplifying z = 0
| -6(x+4)-42=2-38 | | -2+11=13x-3-12x | | y=35+-0.2018x | | y=35-0.2018(x) | | (6xy-3)(3xy+5)= | | 0.9y-0.4y=6.5 | | d-10=-16 | | 4(t-5)+6t=5(2t+4)-11 | | x=(-5i)(-6i) | | -1/7-3/2w=4/5 | | -3(3s-5)-15=-3(8s+1)-3 | | x=(5+7i)-(6-8i) | | x=(5+7i)(6-8i) | | -2/3-1/4v=-1/5 | | 160.03=2.72w+14.84 | | 12(2)+15(2)-9+5=-3(2)+5-9 | | 5X+2X-3Y=13-2 | | 1-2(3x-4)=5x-2(3x-5) | | 1/2=-1/2x-6/5 | | -7/2+6/7x=-8/3 | | -2(3s-5)-10=-3(5s+3)-5 | | .24(18)+0.04x=0.08(24+x) | | 2r^2-6r/r-3 | | 5w^2+7w=6 | | 2p+7=5-(11p+6) | | 5/4+2y=4y-1/4 | | .3(6)+.05x=.15(30+x) | | lx-4l=3 | | 6x^2=12x-16/3 | | 6(v+1)-2v=2(2v+2)-11 | | 7+13y-5=9y+18-4y | | 11/6+1/5t=4 |